2020
DOI: 10.1016/j.sbi.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Structures and regulations of ATM and ATR, master kinases in genome integrity

Abstract: Homologous recombination (HR) is a faithful repair mechanism for double stranded DNA breaks. Two highly homologous master kinases, the tumour suppressors ATM and ATR (Tel1 and Mec1 in yeast), coordinate cell cycle progression with repair during HR. Despite their importance, our molecular understanding of these apical coordinators has been limited, in part due to their large sizes. With the recent development in cryo-electron microscopy, significant advances have been made in structural characterisation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Therefore, assembly of mTORC1 requires the concerted action of CCT (for proper C-terminal folding of Raptor and mLst8) and the Hsp90 TTT-R2TP complex (for mTOR folding). The two-lobed PIKK KD presents several conserved elements: the ATP loop in the N-lobe, and the catalytic and activation loops, as well as the PIKK-regulatory domain (PRD), in the C-lobe [110] ( Figure 8B). The PRD consists of two conserved helices (kinase (K) α9 and Kα10) connected by a divergent loop, termed the PRD insert (PRD-I) [110].…”
Section: Beyond Cell Growth: Tor As a Pikkmentioning
confidence: 99%
“…Therefore, assembly of mTORC1 requires the concerted action of CCT (for proper C-terminal folding of Raptor and mLst8) and the Hsp90 TTT-R2TP complex (for mTOR folding). The two-lobed PIKK KD presents several conserved elements: the ATP loop in the N-lobe, and the catalytic and activation loops, as well as the PIKK-regulatory domain (PRD), in the C-lobe [110] ( Figure 8B). The PRD consists of two conserved helices (kinase (K) α9 and Kα10) connected by a divergent loop, termed the PRD insert (PRD-I) [110].…”
Section: Beyond Cell Growth: Tor As a Pikkmentioning
confidence: 99%
“…1c). Moreover, the PIKK regulatory domain (PRD, aa 4009-4039), which is partially disordered in mTOR and SMG1 (Langer et al, 2020;Yang et al, 2017), and closed in ATM, ATR (Jansma et al, 2020;Williams et al, 2020), and in all other DNA-PKcs and DNA-PK complexes, rotated 115° to expose the substrate binding groove. Complex VI also revealed that the activated DNA-PKcs has a potential binding site for inositol hexaphosphate (IP6), which has been shown to activate DNA-PK and NHEJ (Hanakahi et al, 2000).…”
Section: Results Cryoem Structures Of Dna-pkmentioning
confidence: 99%
“…Multiple structures of other PIKK kinases complexed with accessory subunits, activation cofactors, ATP analogs, and even a substrate peptide have been reported, representing either active mTOR and SMG1 (Langer et al, 2020;Yang et al, 2017) or inhibited ATM and ATR (Jansma et al, 2020;Williams et al, 2020). In all cases the role of the HEAT-repeat structures, which is 5 to 9-fold larger than the kinase domain, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect of 2μ POL30 and elg1Δ on mcd1-1 mutant cells is consistent with the model that even very moderate levels of PCNA is detrimental to genome maintenance. Mec1 (ATR) and Tel1 (ATM) kinases form parallel DNA damage response pathways [81][82][83][84]. To determine…”
Section: Elevated Levels Of Chromatin-bound Pcna (Via 2μ Pol30) Activmentioning
confidence: 99%